Сільська молодь Івано-Франківщини: соціокультурні реалії - Момот, Т. (Народна творчість та етнологія, 2013)
Дослідження присвячене соціокультурним реаліям, у яких живе сільська молодь Косівського району Івано-Франківської області. На основі польових матеріалів охарактеризовано молодіжні проблеми регіону: безробіття, заробітчанство, алкоголізація, девіантна поведінка. Окрему увагу приділено ставленню молоді до старшого покоління. This study considers the socio-cultural realities of rural youth and their living in Kosiv District (Ivano-Frankivsk Region). Based on the field data, there has been given an in-depth description of the region’s youth problems: unemployment, jobbing, alcohol abuse, and deviant behavior. A special attention was paid to the elders’ perception of youth and to comparison of former and current public conduct of young people.